NFκB1: a common biomarker linking Alzheimer's and Parkinson's disease pathology - Cunningham, Adam; Barrett, Emma; Risch, Sebastian; Lee, Peter H. U.; Lee, Chan; Moghekar, Abhay; Patra, Prabir; Shim, Joon W. (Frontiers in Neuroscience, 2025)
IntroductionAlzheimer's disease (AD) and Parkinson's disease (PD) are neurodegenerative disorders characterized by mitochondrial dysfunction and chronic inflammation. The transcription factor NF-κB1 is implicated in both neuroprotective and pro-inflammatory processes, with its activity varying between neurons and glial cells. While previous studies have explored the genetic and epigenetic contributions to these diseases, the infection hypothesis has re-emerged as a potential framework for identifying novel biomarkers and therapeutic targets.MethodsWe conducted bulk RNA sequencing on human postmortem caudate nucleus tissue samples obtained from cognitively normal controls (n = 5), AD patients (n = 6), and PD patients (n = 3). Differential gene expression analysis and pathway enrichment were performed to identify dysregulated signaling mechanisms relevant to neuroinflammation and mitochondrial function.Results and discussionTNFα signaling through the NF-κB pathway was identified as a prominently dysregulated mechanism in both AD and PD samples. Transcript levels of NFE2L2 (NRF2) and NF-κB1 were elevated, coinciding with reduced expression of the mitochondrial transporter gene SLC25A6, suggesting a compensatory response to oxidative stress. Additionally, PLCG2 expression was markedly increased in microglial populations, reflecting heightened immune activation. A significant 10-fold reduction in hemoglobin subunit alpha (HbA1) RNA was observed in disease groups compared to controls, indicating compromised oxygen transport and cellular stress. These findings highlight candidate biomarkers and suggest that therapeutic strategies targeting mitochondrial integrity and neuroinflammation may be effective in AD and PD.